Qur’anic Reading Competence And Worship Practice; Examining Contextual Variations Across Academic Programs - Muttaqin Khabibullah; Hasan Mahfudh; Mudlofar Utsman; Ahmad Mahdi; Gus Malik Imam Sholahuddin; Agil Muhammad; Nur Muhammad Hasib (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2026)
This study aims to examine the relationship between Qur’anic reading competence and students’ worship practice, as well as how this relationship varies across academic programs. The study employed a quantitative approach with a descriptive-correlational and comparative design. The participants consisted of 48 students selected using a total sampling technique. Data were collected through a Qur’anic reading performance test and direct observation of worship practices, and were analyzed using descriptive statistics, Spearman correlation, and the Kruskal–Wallis test to identify variations across groups. The results indicate that students’ Qur’anic reading competence is generally high, while their worship practice is categorized as good. The global Spearman correlation analysis revealed a positive and significant relationship between Qur’anic reading competence and worship practice (p = 0,385, p = 0.007), with a weak to moderate strength. However, contextual analysis showed that this relationship varies across academic programs. A significant moderate relationship was found in the Islamic Economics program (p = 0,522, p = 0.004), while a stronger significant relationship was observed in the Islamic Family Law program (p = 0,645, p = 0.044). In contrast, although a moderate correlation was found in the Islamic Banking program (p = 0,581), it was not statistically significant (p = 0,101). Furthermore, the Kruskal–Wallis test indicated no significant differences in Qur’anic reading competence across programs, but revealed significant differences in worship practice. These findings suggest that the relationship between Qur’anic reading competence and worship practice is neither linear nor universal, but rather influenced by academic context. Therefore, the development of pesantren-based competencies in higher education requires an integrative approach that emphasizes both cognitive aspects and context-sensitive reinforcement of worship practices.